Towards a framework for productivity management employed in a complex hospitality resort - Otto, Ebert Rowan (Stellenbosch : Stellenbosch University, 2025)
Otto, E. R. 2025. Towards a Framework for Productivity Management Employed in a Complex Hospitality Resort. Unpublished doctoral dissertation. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/618f891e-ff2b-4dc8-86be-f5468f5e77c1